2017
DOI: 10.5812/aapm.12738
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Effect of Adding Fentanyl, Sufentanil, and Placebo with Intrathecal Bupivacaine on Duration of Analgesia and Complications of Spinal Anesthesia in Patients Undergoing Cesarean Section

Abstract: BackgroundSpinal anesthesia is the method of choice for most elective and emergency Cesarean sections. To increase the duration of anesthesia and improve the quality of analgesia during and after surgery, intrathecal opioids, as adjuvant drugs, are used in combination with local anesthetics.MethodsThis was a double-blind clinical trial performed on 99 patients. Women were divided into 3 groups of fentanyl, sufentanil, and placebo. For fentanyl group, 12.5 mg of bupivacaine and 25 micrograms of fentanyl; for su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 27 publications
(38 reference statements)
3
22
0
Order By: Relevance
“…Similar results to those of this study [10,23] were found by Trik et al [24] MIGNONSIN D. et al [9] In our study, the adverse effects (nausea, vomiting) were more marked in the Gr II (p = 0.00, p = 0.04). Numerous comparative studies have proved that the existence of nausea and vomiting was due to the presence of opioids in Comparative Study of 2 Doses of Sufentanyl (2.5 Μg versus 5 Μg) in the Rachianesthsia for Cesarean Section the anesthetic solution [4,10,11,25,26,27]. These side effects achieved by adding colloids in pre-filling were opposed to ours according to Siddik et al [28].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Similar results to those of this study [10,23] were found by Trik et al [24] MIGNONSIN D. et al [9] In our study, the adverse effects (nausea, vomiting) were more marked in the Gr II (p = 0.00, p = 0.04). Numerous comparative studies have proved that the existence of nausea and vomiting was due to the presence of opioids in Comparative Study of 2 Doses of Sufentanyl (2.5 Μg versus 5 Μg) in the Rachianesthsia for Cesarean Section the anesthetic solution [4,10,11,25,26,27]. These side effects achieved by adding colloids in pre-filling were opposed to ours according to Siddik et al [28].…”
Section: Discussionsupporting
confidence: 92%
“…They can thus reduce the dosage and the hemodynamic effects of local anesthetics, prolong the action time of the spinal block and finally obtain intense and prolonged postoperative analgesia. have been reported according to the type and dosage of morphine used [5,6,7,8,9,10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The result showed that the use of bupivacaine with 25 μg fentanyl or 2.5 μg sulfentanyl as intrathecal drug can increase the analgesia duration and hemodynamic stability, without causing serious complications. Therefore, this study adopted low dose of bupivacaine (9 mg) and sulfentanyl (2.5 μg) as the intrathecal drug (9) , which not only reduced the incidence of hypotension but also ensured better analgesia effect.…”
Section: Discussionmentioning
confidence: 99%
“…For example, under the conditions of Wilwerth et al study, sufentanil 5μg was the opioid of choice, as compared to fentanyl in combination with hyperbaric bupivacaine in intrathecal anesthesia that was associated with the best quality of anesthesia without increased incidence of side effects ( 3 ). Furthermore, in another study, administering intrathecal hyperbaric bupivacaine plus fentanyl achieved a similar duration of analgesia like sufentanil with faster return of motor block and ambulation, and the authors preferred it as an additive for cesarean section surgery ( 4 ). In addition, Faiz et al studied the effects of adding neostigmine or magnesium sulfate to bupivacaine and concluded that magnesium sulfate is a safe and effective adjuvant to increase the onset time of motor block ( 5 ).…”
mentioning
confidence: 99%